Making sense of low-complexity domains: The 2025 Lasker Basic Science Award - William G. Kaelin (Proceedings of the National Academy of Sciences, 2025)
Up to 10 to 20% of the proteome contains regions with much lower amino acid diversity than would be expected by chance. This year’s Lasker Basic Science Award is given to Steven McKnight and Dirk Görlich for their pioneering work on such low-complexity domains (LCDs). They showed, using a variety of elegant approaches, that such LCDs can form homotypic and heterotypic interactions that lead to reversible phase separations in cells. These phase separations, which in the laboratory manifest as hydrogels and in cells as membrane free structures (liquid condensates) such as P bodies and stress granules, form hubs for molecular processes such as transcription and messenger RNA (mRNA) splicing and also underlie the selectivity of nuclear pore complexes (NPCs), which act a barriers to large molecules unless they are escorted by specific LCD containing nuclear transporters that interact with LCD containing nucleoporins within NPC channels. Naturally occurring LCD mutations linked to neurodegeneration and other diseases cause the formation of irreversible (rather than reversible) LCD polymers, resulting in insoluble, amyloid-like, fibrils, underscoring the critical importance of these domains.